Custom barcoded primers for influenza A nanopore sequencing: enhanced performance with reduced preparation time - Goraichuk, Iryna V.; Suarez, David L. (Frontiers in Cellular and Infection Microbiology, 2025)
Highly pathogenic avian influenza is endemic and widespread in wild birds and is causing major outbreaks in poultry worldwide and in U.S. dairy cows, with several recent human cases, highlighting the need for reliable and rapid sequencing to track mutations that may facilitate viral replication in different hosts. SNP analysis is a useful molecular epidemiology tool to track outbreaks, but it requires accurate whole-genome sequencing (WGS) with sufficient read depth across all eight segments. In outbreak situations, where timely data is critical for controlling the spread of the virus, reducing sequencing preparation time while maintaining high-quality standards is particularly important. In this study, we optimized a custom barcoded primer strategy for influenza A whole-genome sequencing on the nanopore sequencing platform, combining the high performance of the Native Barcoding Kit with the prompt preparation time of the Rapid Barcoding Kit. Custom barcoded primers were designed to perform barcode attachment during RT-PCR amplification, eliminating the need for separate barcoding and clean-up steps, thus reducing library preparation time. We compared the performance of the custom barcoded primer method with the Native and Rapid barcoding kits in terms of read quality, read depth, and sequencing output. The results show that the custom barcoded primers provided performance comparable to the Native Barcoding Kit while reducing library preparation time by 2.3X compared to the Native kit and being only 15 minutes longer than the Rapid kit with better depth of sequencing. Additionally, the custom barcoded primer method was evaluated on a variety of clinical sample types. This approach offers a promising solution for influenza A sequencing, providing both high throughput and time efficiency, which significantly improves the time-to-result turnaround, making sequencing more accessible for real-time surveillance.